Factors Affecting the Quality of Profit of Registered Financial Sector Companies on the Indonesia Stock Exchange (2017-2019) - Wenny Anggeresia Ginting; Cristy Nataline; Winda Wati (Journal of Research in Business, Economics, and Education, 2021)
Banking companies must have good management to achieve the maximum level of profitability, namely by managing the assets under their control to create income, the profitability of a bank describes the ability of the bank concerned to earn a profit during a certain period as well as measuring the performance of a bank. The purpose of this study is to determine the effect of Return on Assets, capital structure, Investment Opportunity Set and Company Size on Earning Quality in financial sector companies listed on the Indonesia Stock Exchange for the 2017-2019 period. Quantitative research methods are in the form of numbers and analyzed statistically and are causal. The population is 61 companies in the financial sector. The sample is 25 companies with data on 75 financial statements. The result is that Return on Assets has an effect on the quality of earnings in financial sector companies listed on the Indonesia Stock Exchange for the 2017-2019 period. Capital Structure, Investment Opportunity Set, and Company Size have no effect on earnings quality in financial sector companies listed on the Indonesia Stock Exchange for the 2017-2019 period. Return On Assets, Capital Structure and Investment Opportunity Set affect earnings quality in financial sector companies listed on the Indonesia Stock Exchange for the 2017-2019 period.